PERAN RADIO KOMUNITAS GEMA SOLIDARITAS SEBAGAI PEMBERDAYAAN MASYARAKAT KETAPANG - Amiruddin. Z Amiruddin.Z (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2017)
Basically the radio refer to three categories: radio private , public radio and radio community. Radio community many springing in the west kalimantan especially in kabupaten ketapang. One of them radio community Gema solidarity who stands in ketapang in january 2005. The arrival of radio community Gema solidarity expected as a medium disseminate culture, tradition, customary peace in the bebagai community of ethnic and religion in kabupaten ketapang. This study aims to study the role of radio community Gema solidarity as community empowerment ketapang. Research methodology it uses approach descriptive qualitative, with using a technique of observation, interviews and documentation. The determination of respondents technique executed is probability sampling as many as five people included in radio Gema management of solidarity. The result of this research known the role of community radio Gema solidarity having uniqueness as “ a house with “ to develop creativity which puts forward the culture of peace is evidenced by a broadcast that having some languages among others malay archipelago, dayak, madura, and chinese. Radio Gema community solidarity have attempted to community empowerment ketapang with scope political empowerment, economic empowerment, social empowerment, empowerment of the environment and cultural empowerment peace. Keywords : The role of radio community, community empowerment